Phytochemical and biological activities of some Iranian medicinal plants - Salome Dini; Qihe Chen; Faezeh Fatemi; Younes Asri (Pharmaceutical Biology, 2022)
Context Due to adverse effects of synthetic compounds, there is a growing interest in utilization of plant-derived natural products in the pharmaceutical and food industries. Iranian endemic medicinal plants widely used in traditional practice have attracted much attention as antibacterial and antioxidant agents.Objective This review attempts to compile the accessible scientific research pertained to phytochemical compounds, antibacterial and antioxidant effects of essential oils obtained from some of the most widely used and distributed medicinal plants in Iran.Methods This review has been compiled using references via reliable databases (Google Scholar, SID and Science Direct) from 2010 to 2020. This literature review was limited to references published in English and Persian languages.Results Based on studies heretofore carried out, essential oils isolated from mentioned medicinal plants exhibited strong antioxidant activity which is attributed to their main phytochemical compounds; thymol, carvacrol, p-cymene and γ-terpinene. In addition, the antibacterial activities of essential oils of most plant species from Apiaceae and Asteraceae families were more susceptible against Gram-positive bacteria; Staphylococcus aureus and Bacillus cereus than Gram-negative bacteria; however, essential oils of other studied plant species manifested similar behaviours against both Gram-positive and -negative bacteria.Conclusions As there is rich ethnobotanical knowledge behind Iranian endemic medicinal plants, further scientific research is required to prove their safety and efficacy. This review revealed that there are numerous valuable medicinal plants adoptable in food and pharmaceutical industries in the near future.